Comprehensive Literature Review of Preoperative Tranexamic Acid for Treatment of Bleeding, Edema, and Ecchymosis in Patients Undergoing Rhinoplasty - Sylvia, Sylvia; Viona, Viona (The Indonesian Journal of General Medicine, 2024)
Background: The literature on the use of tranexamic acid (TXA) in rhinoplasty highlights its efficacy in managing intraoperative bleeding, postoperative edema, and ecchymosis. The foundational study by (Ping et al., 2019) conducted a systematic review and meta-analysis, establishing that TXA significantly reduces blood loss and enhances surgical field quality, which is critical for successful nasal surgeries. This study laid the groundwork for understanding the role of TXA in improving surgical outcomes, particularly in minimizing postoperative complications such as edema and ecchymosis around the eyelids. Literature Review: The article "Role of tranexamic acid in nasal surgery: A systemic review and meta-analysis of randomized control trial" by (Ping et al., 2019) provides a comprehensive evaluation of the efficacy of tranexamic acid (TXA) in reducing bleeding, edema, and ecchymosis in patients undergoing various forms of nasal surgery, including rhinoplasty. Conclusion: In conclusion, the collective evidence from these studies supports the use of TXA in rhinoplasty as an effective means to enhance surgical conditions and patient outcomes. However, there remains a critical need for further research to establish standardized dosing strategies and explore alternative administration routes to fully leverage TXA's potential benefits in this surgical field.